Aerosols in the mortuary. Issue 2 (February 1983) - Newsom, S W; Rowlands, C; Matthews, J; Elliot, C J
Abstract : Air counts in seven mortuaries during necropsies revealed that providing care is taken with washing intestines and close dissection, bacterial numbers are often less than those found in an operating theatre, and relate more to the number of people and movement in the room than the work. The acknowledged hazard of work in the mortuary seems to depend more on contact with infected material, and particularly with splashes on surfaces, than to inhalation of infectious material. Mortuaries should be ventilated, if only to contain the smell, but the recommendations of the Howie code of practice seem more than adequate. Provision of exhaust hoods for close dissection should be considered. Mortuary surfaces should be crack-free and easy to clean, and the room free of needless equipment.